Sistem Pengendali Otomatis Kanopi Pintar Secara Realtime Menggunakan Mikrokontroler ESP 32 Berbasis Web - Atika Sopiah; Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The monitoring and controlling system is a field of technology that plays a major role in the industrial world as well as the equipment used by humans on a daily basis. Some human jobs can be replaced by technology through remote monitoring. This research is intended to make a monitoring system and controlling the canopy in a shop or housing. The purpose of this research is to create an automatic and controlling tool that functions to control the canopy through a web page that is also equipped with a rain sensor, temperature sensor and light sensor which functions to receive input from environmental conditions processed by the esp32 microcontroller, to move the canopy to open and close the canopy. automatically or manually with the help of a servo motor and a web page as a control panel. This system was developed using the PHP programming language, the MYSQL database as data storage and the XAMPP server application, which functions to control the canopy remotely via a wireless network.